A Green Methodology for the Synthesis of Some Regioselective 1, 4‐Disubstituted 1, 2, 3‐Triazoles via Laccase‐Mediated Click Reaction. Issue 26 (11th July 2022) - Gupta, Swati; Singh, Ashmita; Narula, Anudeep K.
Abstract: A novel green efficient methodology was developed for the synthesis of some regioselective 1, 4‐disubstituted‐1, 2, 3‐triazoles through an enzyme laccase ( Trametes Versicolor ) catalyzed reaction. The reaction utilizes the Click chemistry approach for the formation of highly substituted and regioselective triazoles. The methodology is unprecedented in the way that it executes under mild conditions at room temperature using green buffer solvents. An array of substituted triazoles were feasibly synthesized and characterized via spectroscopic techniques. Abstract : The novel, green and efficient methodology was developed for the formation of regioselective 1, 4‐disubstituted‐1, 2, 3 triazoles through an enzyme laccase ( Trametes versicolor ) catalyzed reaction. The reaction utilizes the Click chemistry approach for the formation of highly substituted and regioselective triazoles.